2019
DOI: 10.3390/pharmaceutics11050231
|View full text |Cite
|
Sign up to set email alerts
|

Clotrimazole-Loaded Mediterranean Essential Oils NLC: A Synergic Treatment of Candida Skin Infections

Abstract: The increasing development of resistance of Candida species to traditional drugs represents a great challenge to the medical field for the treatment of skin infections. Essential oils were recently proposed to increase drug effectiveness. Herein, we developed and optimized (23 full factorial design) Mediterranean essential oil (Rosmarinus officinalis, Lavandula x intermedia “Sumian”, Origanum vulgare subsp. hirtum) lipid nanoparticles for clotrimazole delivery, exploring the potential synergistic effects again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 51 publications
(82 reference statements)
2
46
0
Order By: Relevance
“…Since a mixture of a solid lipid (fat) with a liquid lipid (oil) form the lipid phase of the NLC emulsion, a lipid screening assay was firstly performed to select the best solid lipid for the production of NLC. For a successful NLC production, the selection of a proper lipid blend is very important, especially to ensure particle's chemical stability to limit the risk of phase separation over storage time [7,30,54]. Thus, a suitable lipid blend requires (i) the solubility of the active compound (oil) in lipid matrix (solid lipid) to attempt lipid incorporation into lipid nanoparticles, ensuring proper drug loading capacity and encapsulation efficiency; (ii) a major spatial incompatibility of liquid and solid lipids molecules, wherein the oil molecules have no active participation in the solid crystalline matrix of the solid lipid and solid lipid crystals, in turn, are not dissolved in the oil; (iii) stability of lipid phase to chemical degradation; (iv) biodegradable lipids, also capable to produce nanometric particles; and (v) an acceptable toxicological profile, with no production of toxic residues along NLC production process [36,39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since a mixture of a solid lipid (fat) with a liquid lipid (oil) form the lipid phase of the NLC emulsion, a lipid screening assay was firstly performed to select the best solid lipid for the production of NLC. For a successful NLC production, the selection of a proper lipid blend is very important, especially to ensure particle's chemical stability to limit the risk of phase separation over storage time [7,30,54]. Thus, a suitable lipid blend requires (i) the solubility of the active compound (oil) in lipid matrix (solid lipid) to attempt lipid incorporation into lipid nanoparticles, ensuring proper drug loading capacity and encapsulation efficiency; (ii) a major spatial incompatibility of liquid and solid lipids molecules, wherein the oil molecules have no active participation in the solid crystalline matrix of the solid lipid and solid lipid crystals, in turn, are not dissolved in the oil; (iii) stability of lipid phase to chemical degradation; (iv) biodegradable lipids, also capable to produce nanometric particles; and (v) an acceptable toxicological profile, with no production of toxic residues along NLC production process [36,39].…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the above-mentioned issues and to benefit from their biological activities, nanoparticles have been proposed to load EOs for therapeutic use [7,9,30]. Nanoparticles have the advantages of site-specific targeted delivery of bioactive molecules, improving their bioavailability with minimal toxicological events [29,31].…”
Section: Introductionmentioning
confidence: 99%
“…Cell viability, anti-inflammatory, and anti-oxidant activities have been evaluated in vitro, confirming that NLC formulations can be fine-tuned for dermocosmetic applications. These Mediterranean oils can also be used to dissolve drugs in order to increase the loading capacity of NLC [15]. An antifungal NLC formulation, composed of clotrimazole and Lavandula or Rosmarinus as anti-proliferative agents, has been developed with the potential to be used as co-adjuvants in the treatment of non-tumoral proliferative dermal diseases [15].…”
Section: Solid Lipid Nanoparticles (Sln) and The Nanostructured Lipidmentioning
confidence: 99%
“…These Mediterranean oils can also be used to dissolve drugs in order to increase the loading capacity of NLC [15]. An antifungal NLC formulation, composed of clotrimazole and Lavandula or Rosmarinus as anti-proliferative agents, has been developed with the potential to be used as co-adjuvants in the treatment of non-tumoral proliferative dermal diseases [15]. A prolonged in vitro release of clotrimazole could be achieved while in vitro studies against Candida albicans, Candida krusei, and Candida parapsilosis confirmed the increased antifungal effect when using Lavandula or Rosmarinus oils in comparison to the non-loaded oil formulations.…”
Section: Solid Lipid Nanoparticles (Sln) and The Nanostructured Lipidmentioning
confidence: 99%
See 1 more Smart Citation